2014 52nd Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2014
DOI: 10.1109/allerton.2014.7028552
|View full text |Cite
|
Sign up to set email alerts
|

Finite length analysis of caching-aided coded multicasting

Abstract: In this work, we study a noiseless broadcast link serving K users whose requests arise from a library of N files. Every user is equipped with a cache of size M files each. It has been shown that by splitting all the files into packets and placing individual packets in a random independent manner across all the caches, it requires at most N/M file transmissions for any set of demands from the library. The achievable delivery scheme involves linearly combining packets of different files following a greedy clique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 17 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…In this context, recent information theoretic studies have shown that the use of network coding over the wireless backhaul can significantly improve the performance of wireless caching networks by creating cache-enabled coded multicast transmissions useful for multiple users (access points) even if requesting different content. In fact, is has been shown that the use of wireless edge caching and coded multicasting enables multiplicative caching gains, in the sense that the per-user throughput scales linearly with the local cache size [4]- [11]. However, the underlying assumption in existing information theoretic literature on caching networks is that the channels between the content source and the users either exhibit the same qualities or follow a shared error-free deterministic model.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In this context, recent information theoretic studies have shown that the use of network coding over the wireless backhaul can significantly improve the performance of wireless caching networks by creating cache-enabled coded multicast transmissions useful for multiple users (access points) even if requesting different content. In fact, is has been shown that the use of wireless edge caching and coded multicasting enables multiplicative caching gains, in the sense that the per-user throughput scales linearly with the local cache size [4]- [11]. However, the underlying assumption in existing information theoretic literature on caching networks is that the channels between the content source and the users either exhibit the same qualities or follow a shared error-free deterministic model.…”
Section: Introductionmentioning
confidence: 95%
“…While a number of studies have characterized this fundamental tradeoff under error-free channel conditions [4]- [11], only a few recent works have provided first steps towards the characterization of the rate-memory region under a degraded broadcast channel [21], [22]. These studies are however limited to scenarios with only two receivers and unrealistic constraints such as requiring the worst channel receiver to have larger storage capacity.…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations